The birth of a wild God - Ximena Velásquez Sánchez (Pensamiento Palabra y Obra, 2013)
In the eighteenth century, both critics and connoisseurs of art arrivedto a common agreement concerning the particular features that maycharacterize the different artistic practices. Since the Renaissance,one particular question floated in the air: What do dance, theater,music, painting and drawing have in common, so that they might besummarized by a single term? The word “Beauty” was then raised as aflag, providing the public as well as the Academies with a satisfactoryanswer. The mystery was therefore apparently solved, while at thesame time the term “Fine Arts” spread all over the world and becameuniversally accepted. Nevertheless, this agreement would awake thewrath of a particular group of artists, led by Alfred Jarry, who in thelate nineteenth century staged the controversial character “FatherUbú”, in the puppet play King Ubu, a character who, for the very firsttime, dares to utter an obscenity in the theater. The audience, compo-sed of spectators who had developed a passive consumption of art as a means to find acceptance and enjoymentwithin a prestigious social group, were utterly shaken in their seats, only to understand that a new kind of aesthetics was born in the arts, from then on able to pin-point the weaknesses, vices and defects of many respected people.